The Routledge handbook of Hindu temples: materiality, social history and practice - Ray, Himanshu Prabha; Kulshreshtha, Salila; Suvrathan, Uthara (Routledge, 2023)
The temple and royalty -- Temple rituals -- Temple as social space -- Temple landscapes -- The temple and beyond -- The colonial interlude.